The Effect Of Students' Motivation, Emotions, And Cognitive Engagement On English Vocabulary Learning Moderated By Augmented Reality Implementation At School X, Jakarta - Pena, Carlos Andres Camelo; Yugopuspito, Pujianto (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Academic performance in childhood affects students’ adaptability and functionality at School X, Jakarta; it is critical to understand the factors that influence this process. Further, augmented reality (AR) is a technology that merges digital information, such as images, videos, and audio, into actual places, facilitating learning through task pleasure, engagement, and motivation. This study investigates the factors that influence academic achievement in English vocabulary learning using AR implementation at School X, such as motivation, emotions, and cognitive engagement, among students ages 9 to 15. The study involves 52 students in grades five through nine at School X. SmartPLS 4 was used to do the data analysis. The results of this study show that emotions have the largest effect on English vocabulary learning achievement compared to other variables, followed by cognitive engagement, which has the second largest impact. Motivation has a positive effect on English vocabulary learning achievement, although it is not strong. AR also has a positive effect on the relationship between motivation and English vocabulary learning achievement, but it does not have a positive effect on the relationship between emotions and English vocabulary learning achievement. AR has no significant influence on the relationship between cognitive engagement and English vocabulary learning achievement.